Induction of Krüppel-Like Factor 4 Mediates Polymorphonuclear Neutrophil Activation in Streptococcus pneumoniae Infection - Bhattacharyya, Aritra; Herta, Toni; Conrad, Claudia; Frey, Doris; García, Pedro; Suttorp, Norbert; Hippenstiel, Stefan; Zahlten, Janine (Frontiers in microbiology, 2021)
The recruitment and activation of polymorphonuclear neutrophils (PMNs) are of central importance for the elimination of pathogens in bacterial infections. We investigated the Streptococcus pneumoniae -dependent induction of the transcription factor Krüppel-like factor (KLF) 4 in PMNs as a potential regulator of PMN activation. We found that KLF4 expression is induced in human blood-derived PMNs in a time- and dose-dependent manner by wild-type S. pneumoniae and capsule knockout mutants. Unencapsulated knockout mutants induced stronger KLF4 expression than encapsulated wild types. The presence of autolysin LytA-competent (thus viable) pneumococci and LytA-mediated bacterial autolysis were required for KLF4 induction in human and murine PMNs. LyzMcre-mediated knockdown of KLF4 in murine blood-derived PMNs revealed that KLF4 influences pneumococci killing and increases the release of the proinflammatory cytokines tumor necrosis factor α and keratinocyte chemoattractant and decreases the release of the anti-inflammatory cytokine interleukin-10. Thus, S. pneumoniae induces KLF4 expression in PMNs, which contributes to PMN activation in S. pneumoniae infection.